Pathogenesis of Important Virulence Factors of Porphyromonas gingivalis via Toll-Like Receptors - Jia, Lu; Han, Nannan; Du, Juan; Guo, Lijia; Luo, Zhenhua; Liu, Yi (Frontiers in Cellular and Infection Microbiology, 2019)
Periodontitis is a common intraoral infection and is inextricably linked to systemic diseases. Recently, the regulation between host immunologic response and periodontal pathogens has become a hotspot to explain the mechanism of periodontitis and related systemic diseases. Since Porphyromonas gingivalis (P. gingivalis) was proved as critical periodontal pathogen above all, researches focusing on the mechanism of its virulence factors have received extensive attention. Studies have shown that in the development of periodontitis, in addition to the direct release of virulent factors by periodontal pathogens to destroy periodontal tissues, over-low or over-high intrinsic immune and inflammatory response mediated by Toll-like receptors (TLRs) can lead to more lasting destruction of periodontal tissues. It is very necessary to sort out how various cytopathic factors of P. gingivalis mediate inflammation and immune responses between the host through TLRs so as to help precisely prevent, diagnose and treat periodontitis in clinic. This review summarizes the role of three most widely studied pathogenic factors produced by P. gingivalis (lipopolysaccharide, gingipains, pili) and their interactions with TLRs at the cellular and molecular level in the progress of periodontitis.